2018
DOI: 10.3389/fpsyt.2018.00472
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Use and Hypothalamic-Pituitary-Adrenal Axis Functioning in Humans

Abstract: Preclinical studies suggest cannabinoids affect functioning of the hypothalamic-pituitary-adrenal (HPA) axis, but little is known about the effects of marijuana (MJ) use on HPA axis functioning in humans. Since previous work indicates substances of abuse may dysregulate the HPA axis, it is critical to understand how MJ use affects HPA axis activity. Here, we review studies that (a) examined the effects of acute MJ administration on HPA axis functioning, (b) investigated the impact of stress on HPA axis functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
4
21
1
Order By: Relevance
“…While speculative, individuals higher in emotion dysregulation may use cannabis to achieve lower perceived stress, and the HPA axis may play a role in this response. Chronic cannabis use may result in blunted HPA axis reactivity and dampened emotional reactivity to stress at both physiological and psychological levels ( 60 , 61 ), which is in line with the role of the ECS in the HPA axis, mood disorders, and controlling negative affect ( 12 , 19 , 20 , 62 ). While blunted stress and emotional reactivity to stressors could appear beneficial, one must consider that mounting a proper hormonal response to stress is inherently adaptive, as it permits individuals to mobilize energy stores and respond aptly to stressors in the environment ( 63 ).…”
Section: Discussionsupporting
confidence: 53%
“…While speculative, individuals higher in emotion dysregulation may use cannabis to achieve lower perceived stress, and the HPA axis may play a role in this response. Chronic cannabis use may result in blunted HPA axis reactivity and dampened emotional reactivity to stress at both physiological and psychological levels ( 60 , 61 ), which is in line with the role of the ECS in the HPA axis, mood disorders, and controlling negative affect ( 12 , 19 , 20 , 62 ). While blunted stress and emotional reactivity to stressors could appear beneficial, one must consider that mounting a proper hormonal response to stress is inherently adaptive, as it permits individuals to mobilize energy stores and respond aptly to stressors in the environment ( 63 ).…”
Section: Discussionsupporting
confidence: 53%
“…in human studies, cortisol concentration was also elevated in response to THC administration, which presumably could result in depressive behaviors in sensitive individuals [56]. In our study, Another experiment conducted in the frame of the current study also revealed personalitybased alterations in response to THC.…”
Section: Discussionsupporting
confidence: 63%
“…Importantly, acute glucocorticoid elevation results in increased GR expression, however prolonged exposure leads to decreased GR (reviewed in 102 ). As Δ9-THC is reported to increase circulating cortisol/corticosterone levels [103][104][105][106] , we speculate that chronic maternal exposure to Δ9-THC may lead to increased maternal glucocorticoid release and ultimately decreased GR and GLUT1 expression. Future studies are warranted in trophoblast cells to further implicate this direct relationship.…”
Section: Discussionmentioning
confidence: 82%